Effect of once‐weekly dulaglutide on glycated haemoglobin (HbA1c) and fasting blood glucose in patient subpopulations by gender, duration of diabetes and baseline HbA1c. Issue 2 (5th October 2017) - Gallwitz, Baptist; Dagogo‐Jack, Samuel; Thieu, Vivian; Garcia‐Perez, Luis‐Emilio; Pavo, Imre; Yu, Maria; Robertson, Kenneth E.; Zhang, Nan; Giorgino, Francesco
Abstract : Aims: To evaluate the efficacy and safety of dulaglutide 1.5 and 0.75 mg in patients with type 2 diabetes by subgroups of gender, duration of diabetes and baseline glycated haemoglobin (HbA1c) in the dulaglutide clinical development programme (AWARD‐1 to ‐6 and ‐8 clinical trials). Methods: Change in HbA1c was analysed by gender, duration of diabetes (<5, ≥5 years and <10, ≥10 years), and baseline HbA1c (<8.5%, ≥8.5%) in pooled and individual studies. Changes from baseline in weight, hypoglycaemia and gastrointestinal adverse events were evaluated for individual trials. Results: In the pooled analysis of patients treated with dulaglutide 1.5 mg at 6 months, the reductions in HbA1c from baseline were similar across gender (men: least squares [LS] mean −1.26% [95% confidence interval CI −1.36, −1.16]; women: LS mean −1.33% [95% CI −1.43, −1.24]) and among duration of diabetes subgroups (<5 years: LS mean −1.32% [95% CI −1.43, −1.22]; ≥5 and <10 years: LS mean −1.33% [95% CI −1.43, −1.22]; ≥10 years: −1.24% [95% CI −1.35, −1.14]). Patients with baseline HbA1c ≥8.5% had greater HbA1c reductions than patients with baseline HbA1c <8.5%, (≥8.5%: LS mean −1.86% [95% CI −1.97, −1.75]; <8.5%: LS mean −1.02% [95% CI −1.12, −0.93]). Reductions in fasting blood glucose (FBG) were consistent with HbA1c changes. Similar results were observed with dulaglutide 0.75 mg. In general, body weight changes were similar among duration of diabetes and in baseline HbA1c subgroups, respectively; women had a numerically greater weight loss or less weight gain than men with both dulaglutide doses. There was no clinically meaningful difference in hypoglycaemia trends by gender or duration of diabetes. Hypoglycaemia incidence and rate were generally lower in patients with baseline HbA1c ≥8.5% than in those with <8.5%, except for the AWARD‐4 study (combination with mealtime insulin). Conclusions: Across the AWARD studies, dulaglutide demonstrated significant improvements in glycaemic control irrespective of gender, duration of diabetes, or baseline HbA1c, with greater HbA1c and FBG reductions in patients with a higher baseline HbA1c. Dulaglutide was well tolerated, with a safety profile similar to other glucagon‐like peptide‐1 receptor agonists.